Local Wisdom: a Sociology of Communication Analysis in West Manggarai - Duryatmo, Sardi; Sarwoprasodjo, Sarwititi; Lubis, Djuara P; Suhartijo, Didik (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
The utilization of medicinal plants is the local wisdom of the people of Waesano Village, Sanonggoang, West Manggarai Regency. Local wisdom is a form of culture that can be defined as the whole system of ideas, action, and results of human’s work in social life that is possessed through learning. This qualitative research that was carried out in Waesano Village, Sanonggang, West Manggarai Regency, East Nusa Tenggara Province, uses communication ethnographic method to explain the connection between categories in the research. Ethnography of communication seeks to portray human ways of life. This study aim to reveal ritual communication in Waesano Village which play a role the enculturation of local wisdom in the use of medicinal plants. Research result prove that local wisdom in form of the utilization of medicinal plants consists of identifying the variant of a medicinal plant, how to pick, how to process, and consumption dose. Inheritance or enculturation of a local wisdom in form of medicinal plant utilization is through ritual communication such as between father and child, parents-in-law and children-in-law. Another form of communication which plays a role in the enculturation process are students that receive medicinal plant lesson from teacher who teaches Local Content subject of Environmental Education and Conservation. Having the variety of communication processes, the local wisdoms are expected to be able to survive in Waesano.